Cultural Economy and Television in Jamaica and Ghana: #decolonization2point0 - Hickling Gordon, Deborah (Palgrave Pivot, 2020)
This book proposes contemporary decolonization as an approach to developing cultural economies in the Global South. This book represents the first critical examination and comparison of cultural and creative industries (CCI) and economy concepts in the Caribbean and Africa.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Ghana (corpus analysé); Jamaïque (corpus analysé); Jamaïque (lieu de production du savoir); _Nettoyé

Black Art: Ancestral Legacy : The African Impulse in African-American Art. - Dallas Museum of Art (Dallas Museum of Art, 1990)
For the first time, a major exhibition examines the impact of African culture on black artists, both trained and self-taught, in a stunning range of 157 works which are variously bold, witty, historical, and mysterious. 49 biographical outlines; 320 illustrations, 170 in full color.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé